Sexting, Self-esteem, and Social Media: A Comparison among Frequent, Occasional, and Non-sexting Italian Adolescent Girls - Valeria; Valeria; Stefano; Nadia; Francesca (Psychology in Russia: State of Art, 2023)
Background. The phenomenon of sexting consists of sending and sharing sexual images, videos, or messages using smartphones and social networks. Sexting is spreading dangerously among adolescents who share private and explicit sexual content, ignoring the negative and risky consequences associated with this behavior. According to recent literature, sexting behavior is strongly related to the participants’ level of self-esteem and social media’s influence on them. Objective. Our study was a descriptive community-based study focused on the central-south Italian context, which aimed to investigate sexually risky behavior and the main motivations for sexting, and to compare differences in self-esteem and social media’s influence among three groups of Italian girls: non-sexters, occasional sexters, and frequent sexters. Design. Our research involved 569 Italian girls (14–19 years old) who completed the following questionnaires: the Questionnaire on Health and Sexual Behavior; the Sexting Behavior Scale; the Multidimensional Self-Concept Scale; and the Sociocultural Attitudes Toward Appearance Questionnaire-3. Results. Our results showed that most participants sexted with their partner, and had a responsible attitude toward sexuality and kept sexual risk low. Moreover, frequent sexters had higher scores on social media’s influence relative to the internalization of the body image and model for beauty and athleticism, as well as lower levels of global, academic, and competence self-esteem. Conclusion. Our results could promote interventions in the school context in order to: a) improve awareness among youth about social media use, sexting, and safe sexuality; b) reduce the risk associated with sexting and the influence of social networks; and c) stimulate reflections by teachers and parents on adolescents’ sense of identity and self-esteem.